Euronet Lab, A Cloud V-Lab Enviroment - Correia, Raúl Cordeiro (2014)
In this paper we present a proposal for the creation of a European V-labs web space. In its essence it would result in an open online laboratory, with a primarily practical nature. In this laboratory students will have the opportunity to develop skills in the “know-how-to-do” area, enabling them to conduct a series of practical experiences in “try-out” philosophy that will substantiate and consolidate all knowledge that the students acquired in lectures. It is quite possible that these resources aren’t available in all universities and institutions, specifically in the university where the student is. This environment provides substance to the Directive stated in the declarations of Bologna and Prague that expresses “the teaching process is therefore student-centered”, strengthening the final pedagogical aim of “learning to learn”, as lifelong learning is assumed as an indispensable stage. What we propose is the creation of a virtual environment for e-learning where a series of virtual labs in many areas of electronics, automation and robotics are available, in this environment it will do possible for any student of any of these universities to scheduling of experience in any institution that belongs to this cloud, and thus can perform is work for anytime that will be available and with technical resources available or not available in its own university.